Progesterone after previous preterm birth for prevention of neonatal respiratory distress syndrome (PROGRESS): a randomised controlled trial - Flenady Vicki; McPhee Andrew J; Crowther Caroline A; Dodd Jodie M; Robinson Jeffrey S (BMC Pregnancy and Childbirth, 2009)
Abstract Background Neonatal respiratory distress syndrome, as a consequence of preterm birth, is a major cause of early mortality and morbidity during infancy and childhood. Survivors of preterm birth continue to remain at considerable risk of both chronic lung disease and long-term neurological handicap. Progesterone is involved in the maintenance of uterine quiescence through modulation of the calcium-calmodulin-myosin-light-chain-kinase system in smooth muscle cells. The withdrawal of progesterone, either actual or functional is thought to be an antecedent to the onset of labour. While there have been recent reports of progesterone supplementation for women at risk of preterm birth which show promise in this intervention, there is currently insufficient data on clinically important outcomes for both women and infants to enable informed clinical decision-making. The aims of this randomised, double blind, placebo controlled trial are to assess whether the use of vaginal progesterone pessaries in women with a history of previous spontaneous preterm birth will reduce the risk and severity of respiratory distress syndrome, so improving their infant's health, without increasing maternal risks. Methods Design: Multicentred randomised, double blind, placebo-controlled trial. Inclusion Criteria: pregnant women with a live fetus, and a history of prior preterm birth at less than 37 weeks gestation and greater than 20 weeks gestation in the immediately preceding pregnancy, where onset of labour occurred spontaneously, or in association with cervical incompetence, or following preterm prelabour ruptured membranes. Trial Entry & Randomisation: After obtaining written informed consent, eligible women will be randomised between 18 and 23+6 weeks gestation using a central telephone randomisation service. The randomisation schedule prepared by non clinical research staff will use balanced variable blocks, with stratification according to plurality of the pregnancy and centre where planned to give birth. Eligible women will be randomised to either vaginal progesterone or vaginal placebo. Study Medication & Treatment Schedules: Treatment packs will appear identical. Woman, caregivers and research staff will be blinded to treatment allocation. Primary Study Outcome: Neonatal Respiratory Distress Syndrome (defined by incidence and severity). Sample Size: of 984 women to show a 40% reduction in respiratory distress syndrome from 15% to 9% (p = 0.05, 80% power). Discussion This is a protocol for a randomised trial. Clinical Trial Registration Current Controlled Trials ISRCTN20269066